2021
DOI: 10.2147/jaa.s323504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Childhood Exposure to a Farming Environment on Age at Asthma Diagnosis in a Population-Based Study

Abstract: Purpose: Asthma is a heterogeneous disease, and factors associated with different asthma phenotypes are poorly understood. Given the higher prevalence of farming exposure and late diagnosis of asthma in more rural Western Finland as compared with the capital of Helsinki, we investigated the relationship between childhood farming environment and age at asthma diagnosis. Methods: A cross-sectional population-based study was carried out with subjects aged 20-69 years in Western Finland. The response rate was 52.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Childhood exposure to farming environment was significantly more common in N-ERD than asthma without N-ERD, whereas a nonsignificant trend was seen compared to healthy controls. In our recent study, childhood exposure to farming environment had lower odds of early-diagnosed asthma and higher odds of late-diagnosed asthma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood exposure to farming environment was significantly more common in N-ERD than asthma without N-ERD, whereas a nonsignificant trend was seen compared to healthy controls. In our recent study, childhood exposure to farming environment had lower odds of early-diagnosed asthma and higher odds of late-diagnosed asthma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it did increase the odds for having asthma diagnosed at late age (defined as age >40). 32 It has been speculated if adult-onset asthma would be a relapse rather than initiation of the disease and whether asthma symptoms beginning in adulthood would have originated in childhood. 33,34 However, subjects with adult-onset versus child-onset asthma seem to have different basic characteristics, such as gender and BMI, 2,14 which challenges this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have proved that there is a codependent relationship between gut microbiota and immune system development [66][67][68][69][70][71][72][73][74][75][76]. [77], preterm birth [78], formula feeding [79], and cesarean section delivery [80] increase the development of asthma in infants, while living in a big family [81] and farming environment [82] decrease asthma incidents. Increased birth weight [83] and combined feeding of breast milk and formula [84] increase food allergy development in childhood.…”
Section: Non-maternal Influencing Factors For the Development Of Alle...mentioning
confidence: 99%
“…Exposing children to a diverse microbial environment is important for establishing a healthy immune response. Studies have shown that children who grow up in farms [82,103,116], where they have much more contact with microorganisms compared to urban environments, have a lower rate of developing allergic diseases. Studies have also indicated that early life respiratory tract colonization with certain bacteria, such as Streptococcus, Moraxella, or Haemophilus, increase the severity of lower respiratory viral infection in the first year of life, and the risk of developing asthma symptoms later in life [117].…”
Section: The Role Of Lung and Gut Microbiota In Asthmamentioning
confidence: 99%
See 1 more Smart Citation